On the Attitudinal Consequences of Being Mindful: Links Between Mindfulness and Attitudinal Ambivalence. (April 2017) - Haddock, Geoffrey; Foad, Colin; Windsor-Shellard, Ben; Dummel, Sebastian; Adarves-Yorno, Inmaculada
A series of studies examined whether mindfulness is associated with the experience of attitudinal ambivalence. Studies 1A and 1B found that mindful individuals expressed greater comfort holding ambivalent views and reported feeling ambivalent less often. More mindful individuals also responded more positively to feelings of uncertainty (as assessed in Study 1B). Study 2 replicated these effects and demonstrated that mindful individuals had lower objective and subjective ambivalence across a range of attitude objects but did not differ in attitude valence, extremity, positivity/negativity, strength, or the need to evaluate. Study 3 showed that the link between greater ambivalence and negative affect was buffered by mindfulness, such that there was no link between the amount of ambivalence and negative affect among more mindful individuals. The results are discussed with respect to the benefits of mindfulness in relation to ambivalence and affect.